George and Martha Round and Round - James Marshall
More wonderful adventures of George and Martha, two lovable hippos with a strong friendship. One hippo's trash is another hippo's...cuckoo clock? George and Martha may be best friends, but that doesn't mean they like all the same things. The two hippos exercise both their imaginations and forgiveness as they deepen their bond of friendship in this addition to the classic children's series. A man with a talent for friendship, James Marshall defined its very essence in his stories about the world$1 (Bs two best friends. Each of these five brief tales is filled with humor, and James Marshall$1 (Bs drawings are guaranteed to spark feelings of empathy, delight, and self-recognition.s